AKURASI ARAH KIBLAT MASJID MENGUNAKAN METODE TRIGONOMETRI BOLA DI KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - lusi ratna sari; ernawati ernawati; endah purwaningsih (JURUSAN GEOGRAFI FIS UNP, 2019)
Abstract Facing the Qiblah is a valid condition of prayer based on the agreement (ijma ') of the scholars. the direction of the Qibla with a difference of 1o will cause a shift of about 145 km to the north or south of the Ka'bah. Based on this, the accuracy of the Qibla direction is very important because facing the Qibla is a legitimate condition for prayer. This study aims to determine the method and level of Qibla direction accuracy in IV Jurai sub-district. This type of research is quantitative with the research subject being a mosque in Subdistrict IV Jurai with a sampling technique that is purposive sampling, sampling mosques built under 2010. Data collection is carried out directly in the field using a brunton geological compass measuring instrument and questionnaire. The data analysis technique uses the spherical trigonometry formula, while the percentage uses descriptive analysis. The results showed (1) the determination of the Qibla direction in the IV Jurai sub-district in general using a method based on the opinion of scholars, based on the direction of the sun and rising, aiming west, based on the northwest direction, using the Qibla compass, based on the direction of the old mosque, and compass by Ministry of Religion (2) Accuracy of Qibla direction of mosques in IV Jurai sub-district, 12% accurate, 15% tolerated, 73% inaccurate. Suggestions that can be conveyed in connection with the results of research on mosque administrators for mosques whose direction of qibla is not appropriate are recommended to shift the direction of the prayer mat towards the right qibla. Keywords: Qibla, mosque, accuracy, spherical trigonometry